TINJAUAN YURIDIS TERHADAP PERATURAN DAERAH NOMOR 3 TAHUN 2015 TENTANG PENATAAN DAN PEBERDAYAAAN PEDAGANG KAKI LIMA DI KOTA BAUBAU - La Ode Abdul Hamid; Sitti Aisyah (Jurnal Ilmu Hukum Kanturuna Wolio, 2021)
This research aimed at knowing the juridical comtempletation on local regulation Number 3 in 2015 about the Organization and Empowerment of the Sidewalk Trader in Baubau City and what are the factors to be the challenges in the application of local regulation. Meanwhile, the theoretical significance of the research was to give a contribution and thought for the development of laws, especially the constitutional (staatsrecht) primarily on the development of laws, of local government, this research was practically to give a contribution and thought sientifically to the government or local government, primarily concerning with the the Organization and Empowerment of the Sidewalk Trader in Baubau City. The method of the research used was explanatory and description analysis, namely the recearch which did the investigation and gradually gave a description concerning with the juridical comtempletation on Local Regulation Number 3 in 2015 about the Organization and Empowerment of the Sidewalk Trader in Baubau City. Based on the prolem statements, significances, and the method of the research used, the researcher concluded that the Local Regulation Number 3 in 2015 in the Organization and Empowerment of the Sidewalk Trader has not effectively been done to the city society and still needed to be studied to be aspirative, while the factors to be the challenges in the application of the Local Regulation Number 3 in 2015 about the about the Organization and Empowerment of the Sidewalk Trader in Baubau City and concerning with empowerment of it was still much far from the society hope of Sidewalk Trader in Baubau City.